DEVELOPMENT OF MATHEMATICS STUDENT WORKSHEET WITH THINK TALK AND WRITE (TTW) APPROACH TO INCREASE STUDENT MATHEMATICAL COMMUNICATION SKILLS IN SMK NEGERI 14 MEDAN - Simbolon, Mula Tua Elia; Al Idrus, Said Iskandar (PHI: Jurnal Pendidikan Matematika, 2024)
The mathematical communication skills of students at SMK Negeri 14 Medan are quite low and this can be seen from the results of observations made by researchers on students. Therefore this research was conducted to develop a student worksheet that can be used by students and teachers in the learning process. This student worksheet uses the Think Talk and Write approach and is considered capable of being valid, practical, and effective in helping students learn and improving students' mathematical communication skills. research is a type of research and development research using the ADDIE model. the ADDIE model consists of the Analysis, Design, Develop, Implementation, and Evaluation stages. from the results obtained it was found that the student worksheet was valid with a score of 88%. then this student worksheet is also practical to use as seen from the results of the student questionnaire and teacher questionnaire. then the effectiveness of student worksheets is also classified as medium in improving students' mathematical communication skills seen from the N-Gain obtained by students is 5.8